Bacterial synthesis of polysialic acid lactosides in recombinant Escherichia coli K-12. (3rd August 2016) - Richard, Emeline; Buon, Laurine; Drouillard, Sophie; Fort, Sébastien; Priem, Bernard
Abstract: Bacterial polysialyltransferases (PSTs) are processive enzymes involved in the synthesis of polysialic capsular polysaccharides. They can also synthesize polysialic acid in vitro from disialylated and trisialylated lactoside acceptors, which are the carbohydrate moieties of GD3 and GT3 gangliosides, respectively. Here, we engineered a non-pathogenic Escherichia coli strain that overexpresses recombinant sialyltransferases and sialic acid synthesis genes and can convert an exogenous lactoside into polysialyl lactosides. Several PSTs were assayed for their ability to synthesize polysialyl lactosides in the recombinant strains. Fed-batch cultures produced α-2, 8 polysialic acid or alternate α-2, 8–2, 9 polysialic acid in quantities reaching several grams per liter. Bacterial culture in the presence of propargyl-β-lactoside as the exogenous acceptor led to the production of conjugatable polysaccharides by means of copper-assisted click chemistry.